Development of mobile application that detects phishing Messages to decrease the percentage of data theft during the COVID-19 pandemic - Meneses Claudio, Brian Andreé (2022)
The COVID-19 pandemic has established not only a health emergency, but has generated an emergency in the control of personal data of all those people who make use of technological means, which increased the activity of phishing which consists of the theft of personal data through the circulation of false information through the different social networks, in addition, the circulation with messages related to the cure of this disease only for the theft of data. This research develops a mobile application that detects malicious URLs found within the content of textmessages. The developed application performs an analysis of the URLs according to the database thatis updated with each attack detected, performing a blocking of the content and notifies the user of the actions that canbetaken, with this the theft of the personal data of the users is avoided. This application is very useful for all those people who use mobile equipment (mobile) and haveno knowledge of these types of attacks, since they are likely to perform the actions that the perpetrators foresee for the obtaining of their personal data, so this application provides a means of security against these types of phishing attacks.